Intelligent examination timetabling system using hybrid intelligent water drops algorithm - AlDeeb, Bashar A.; Md Norwawi, Norita; Al-Betar, Mohammed A.; Jali, Mohd Z. (2015)
This paper proposes Hybrid Intelligent Water Drops (HIWD) algorithm to solve Tamhidi programs uncapacitated examination timetabling problem in Universiti Sains Islamic Malaysia (USIM).Intelligent Water Drops algorithm (IWD) is a population-based algorithm where each drop represents a solution and the sharing between the drops during the search lead to better drops.The results of this study prove that the proposed algorithm can produce a high quality examination timetable in shorter time in comparison with the manual timetable.